2019
DOI: 10.1016/j.cmet.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

A “Connexin” Responsible for the Fatal Attraction of Cancer to Bone

Abstract: Tumor cell interactions with the bone microenvironment are vital for the establishment and progression of bone metastases. Recently in Cancer Cell, Wang et al. (2018) showed that cells of the osteoblast lineage are critical for the delivery of calcium to tumor cells through gap junctions, pointing toward potential therapies for bone metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…During this process, the release of growth factors, such as transforming growth factor-β (TGF-β), vascular endothelial growth factor (VEGF), insulin-like growth factors (IGFs), BMPs, and calcium, is ongoing in the bone microenvironment. It was proven that the increase in intracellular calcium levels among BC cells could interfere with the osteogenic function and facilitate survival [43]. TGF-β is a pleiotropically expressed multifunctional cytokine that controls tissue homeostasis by regulating cellular apoptosis, proliferation, and differentiation [45].…”
Section: Survivalmentioning
confidence: 99%
“…During this process, the release of growth factors, such as transforming growth factor-β (TGF-β), vascular endothelial growth factor (VEGF), insulin-like growth factors (IGFs), BMPs, and calcium, is ongoing in the bone microenvironment. It was proven that the increase in intracellular calcium levels among BC cells could interfere with the osteogenic function and facilitate survival [43]. TGF-β is a pleiotropically expressed multifunctional cytokine that controls tissue homeostasis by regulating cellular apoptosis, proliferation, and differentiation [45].…”
Section: Survivalmentioning
confidence: 99%
“…In particular, the abundant calcium in the bone matrix can attract the calcium-sensing receptor-expressing breast cancer cells to the bone. Furthermore, Wang et al (2018) showed that the increased intracellular calcium concentration in metastatic breast cancer cells induced by connexin 43 can disturb the osteogenic niche and promote survival (Waning et al, 2019). Furthermore, the bone microenvironment promotes breast cancer cells to transit to a migratory phenotype with new malignant capacities.…”
Section: Adhesion and Survivalmentioning
confidence: 99%
“…Many clinical diseases can lead to bone defects and reduced bone formation, including fractures (Matsumoto et al, 2010), bone tumors (Waning et al, 2019), osteoporosis (Cao et al, 2012), and so on. The commonly used treatments, such as bone transplantation, are still very limited.…”
Section: Application Of Msc-derived Exosomes In Bone Tissue Engineeringmentioning
confidence: 99%